2018
DOI: 10.1007/s13205-018-1329-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evaluation of microorganisms for biodegradation of agricultural plastic film

Abstract: Three isolates (HK1, GSDM02, and GSDM15) were tested for effectiveness in biodegradation of plastic films. Isolates were screened by plate on carbon-free medium and by using the clear-zone formation test. Their biodegradation ability was analyzed based on: film weight reduction, pH change of the fluid medium, a soil microbial biomass carbon test, scanning electron microscopy (SEM), and Fourier transform infrared spectrometry (FTIR). Polyvinyl alcohol (PVA) clear-zone and film weight reduction results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…SEM analysis of polymer biodegradation by Penicillium simplicissimum showed the formation of cavities and physical structural changes in the polymer (Sowmya et al 2015). Our FTIR findings on PVA biodegradation principal spectral peaks including their common functional groups, were similar to findings obtained in previous studies (Ullah et al 2019;Zhang et al 2018). In a study by Nwogu et al (2012), degradation of plastic using mushrooms was also confirmed via FTIR analyses.…”
Section: Discussionsupporting
confidence: 88%
“…SEM analysis of polymer biodegradation by Penicillium simplicissimum showed the formation of cavities and physical structural changes in the polymer (Sowmya et al 2015). Our FTIR findings on PVA biodegradation principal spectral peaks including their common functional groups, were similar to findings obtained in previous studies (Ullah et al 2019;Zhang et al 2018). In a study by Nwogu et al (2012), degradation of plastic using mushrooms was also confirmed via FTIR analyses.…”
Section: Discussionsupporting
confidence: 88%
“…However, the specific complex involved in toluene degradation in PM1 remains unknown (Deeb et al, 2001). The only genome lacking expected POPs belonged to the strain Bacillus amyloliquefaciens HK1, despite experimental evidence of its capability to degrade PVA (Zhang et al, 2018). This result suggested that this isolate likely has proteins involved in PVA degradation that are not currently present in our database.…”
Section: Resultsmentioning
confidence: 99%
“…Varying CAZyme profiles of intestinal microbes may had different capabilities of carbohydrate metabolism [42]. Comparison of CAZyme genes in five B. amyloliquefaciens strains, including TL106, HK1, EA19, LL3 and XH7 revealed that B. amyloliquefaciens TL106 had more types of CAZymes genes than the other four strains [43][44][45][46]. GH genes were took a large part in the genome of B. amyloliquefaciens, consistent with those of the genome of Aspergillus fumigatus Z5, which showed highly efficient cellulose-degradation capability [47].…”
Section: Discussionmentioning
confidence: 99%